Pemanfaatan E-Learning Sebagai Media Pembelajaran Mahasiswa - Aqsal Fawwazi Satrio Wibowo; Margaretha Evi Yuliana (Journal Of Informatics And Busisnes, 2024)
Innovation in learning models is needed to improve the quality of learning and students do not experience boredom. Therefore, e-learning-based learning is implemented which is one of the learning models supported by the use of information technology (IT). The e-learning system has many models with various features including edmodo, moodle and google classroom. With the existence of various e-learning systems, students become more independent and creative. While for teachers, it makes it more innovative and easier to update materials or teaching models according to the demands of the times. In addition, it also makes it easier to control student assignments. However, with the existence of various e-learning systems, it is not yet fully effective in improving learning, this is because in the process of applying e-learning requires a stable internet connection in order to run smoothly, besides that teachers do not fully know how to operate e-learning, comprehensive training is needed for teachers so that they can utilize e-learning optimally.